Prevalence Of Traumatic Dental Injuries In Presence Of Oral Habits Among Preschoolers -an Institutional Based Retrospective Study. - M, ASHFAQ AHMED; GURUNATHAN, DEEPA GURUNATHAN; P, SARAVANA DINESH.S. (The journal of contemporary issues in business and government, 2021)
Traumatic dental injuries are most frequent during the first 10 years of life, it decreases with increase in age, and are very rarely seen after the age of 30. Etiologic factors are very much linked to falls due to accidents or steps are the most common cause of oral injuries. The management of traumatic dental injuries to the primary teeth differs from that used for permanent dentition. There is a close relationship between the apex of the root of the injured primary tooth and the underlying permanent tooth germ. Thus the aim of the study is to analyse the prevalence of traumatic dental injuries in primary teeth among children in the age group of 1- 6 years. A retrospective analysis was done using dental archiving software present in the department of pedodontics where patients intraoperative photographs were checked for cross verification. The graphs and tables were done using SPSS software version 23 and chi square test was done. The results of the study showed that higher prevalence of traumatic dental injury was seen in females (25%) when compared to males (p>0.05), statistically not significant. Subjects with avulsion(33.33%) had oral habits of mouth breathing and subjects took minimum 1 day (16.67%) to report for treatment (p>0.05) statistically not significant.